TASK-BASED LEARNING IN ENGLISH AS A FOREIGN LANGUAGE (EFL) CLASSROOM: WHAT, HOW AND WHY? - Muhammad Badrus Sholeh; Kisman Salija; Sahril Nur (English Education Department, 2021)
Task-based Learning is increasingly prevalent worldwide. It emphasizes on authentic language use and asks students to perform meaningful tasks. English teaching by tasks is considered useful in a language classroom because the students are expected to learn better the target language when tasks are used in language teaching. The tasks are designed to establish a real language use objectives and to create a natural language acquisition setting. Task-based Learning, often considered being the powerful Communicative Language Teaching (CLT) version, gradually becoming second-language learning. This article describes the Task-based Learning definition, to recognize the principles and characteristics of Task-based Learning, to examine how to implement Task-based Learning in the English classroom, and to clarify the advantages of this approach.